Dynamics of Islamic Boarding School Learning in the Digital Era: Between Preserving Tradition and Adapting Technology at Al-Intiqol Islamic Boarding School and Al-Ittihad Islamic Boarding School in Cianjur. - Ruslan Abdul Gani; Nur Alim Abdul Gani (Doctoral Program of Social Science Pasundan University, 2026)
This study aims to examine the dynamics of Islamic boarding school learning in the digital era by highlighting how Islamic boarding schools strive to maintain scholarly traditions while responding to technological developments. The research focuses on the Al-Intiqol Islamic Boarding School in Cianjur, a representative of traditional Islamic boarding schools that emphasize the preservation of tradition, and the Al-Ittihad Islamic Boarding School in Cianjur, a modern Islamic boarding school that integrates technology into the learning process without losing the essence of Islamic boarding school education. This research uses a qualitative approach with a case study method that focuses on the dynamics of learning in Islamic boarding schools in the digital era, particularly in balancing the preservation of tradition and adaptation to technology. Data were collected through in-depth interviews with the leaders of the Al-Intiqol Cianjur Islamic boarding schools and the Al-Ittihad Cianjur Islamic boarding schools, participant observation of the teaching and learning process, and analysis of relevant documents. The sampling technique was carried out purposively to obtain informants who have direct knowledge and experience related to the phenomenon studied. Data analysis was carried out descriptively-qualitatively with the stages of data reduction, data presentation, and drawing conclusions, which were validated through sources to ensure the validity of the research findings. The research results show that Al-Intiqol Islamic Boarding School emphasizes traditional teaching methods based on yellow books, sorogan, and bandongan, but has begun to allow for limited use of digital media to support learning. Meanwhile, Al-Ittihad Islamic Boarding School has successfully developed an adaptive learning model by combining the formal curriculum, digital technology, and traditional methods, creating a synergy between preserving tradition and educational innovation. This study concludes that the dynamics of Islamic boarding schools in the digital era are not simply a matter of choosing between tradition and modernization, but rather an effort to blend the two to remain relevant to the needs of the times while maintaining the identity of Islamic boarding schools as centers of Islamic religious learning.